Hubungan Kelentukan Pergelangan Tangan terhadap Kemampuan Menggiring Bola pada Permainan Bola Basket di Medan - Muliati, Muliati; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Damanik, Rodearni (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2025)
Physical fitness of a basketball player is an absolute requirement in running a game. Flexibility is one of the components of physical fitness needed by players to produce proper basketball techniques such as dribbling or dribbling techniques. This study aims to determine how the contribution or relationship of wrist flexibility (flexion) to dribbling ability in basketball games. This study was conducted on adolescents with an age range of 15-17 years. This research is a quantitative research without giving any treatment or training. The research sample consisted of 25 students who were members of the basketball extracurricular which were selected by purposive sampling based on inclusion and exclusion criteria. Wrist flexibility was measured using a goneometer, while the dribbling test was used to measure the sample's ability to dribble. To test the hypothesis in this study, using the Pearson product moment correlation test to determine the relationship between the two variables with the results obtained a significant value of 0.000 which indicates a correlation between the two variables and the correlation coefficient of 0.728 which means the relationship between the two variables is strong. The correlation coefficient from the results of data analysis is negative, which means that the resulting correlation is inversely proportional so that the higher the wrist flexibility, the better the ability to dribble.